Ag-doping on ZnO support mediated by bio-analytes rich in ascorbic acid for photocatalytic degradation of dipyrone drug. (October 2018) - Chelli, Venkatanarasimha Rao; Golder, Animes Kumar
Abstract: The analytes such as ascorbic acid (AA) present in Sechium edule were extracted (294 mg AA kg −1 fruit) in an aqueous media for its potential application for Ag-doping onto wurtzite ZnO. The bandgap of ZnO was decreased to 2.85 eV at the optimal Ag-loading of 1.18% (w/w) against 3.13 eV for the control catalyst without using the analytes and, the commercial AA only could reduce the bandgap to 2.91 eV. The saturation photo-electrochemical current density (46.68 mA cm −2 ) at Eanode  ≥ 0.31 V vs. Ag/AgCl was almost double than pristine ZnO under visible light illumination ( λ mean  = 525 nm, 18 K lux) and, the current density was insignificant in the dark. The doped catalyst exhibited the maximum 79.5% degradation (71% COD removal) of an anti-analgesic drug, dipyrone (100 μg L −1 dipyrone, catalyst 100 mg L −1 ) resulted from the formation of O2 − radical (g-factor of 2.002–2.008) and paramagnetic oxygen vacancies (g-factor of 2.020) and, no effect of dye-sensitization was noted. The highest quantum yield was found to be 34.7%. The catalyst loss was 6% after the fourth cycle and the dipyrone degradation was reduced to 70.8%. Graphical abstract: Image 1 Highlights: Bio-inspired Ag-doping reduced band gap of ZnO to 2.8 eV. Ag-doping intensified O2 − formation and oxygen vacancies Quantum yield of dipyrone drug decomposition of 35.77% at λmean  = 525 nm using doped ZnO. Photoelectrochemical response confirmed reduction in e − /h + recombination with Ag-doping on ZnO. Saturation photocurrent density with doped catalyst of 46.68 mA/cm 2 at 0.31 V vs. Ag/AgCl.